PENGARUH HARGA DAN PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN ALAT-ALAT LISTRIK (PANEL) PADA PT. ANDALAS CITRA ELEKTRINDO - Tambunan, Elisabet (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
This study aims to determine the effect of price and advertising on the decision to return electrical equipment (panels) at PT. Andalas Citra Elektrindo. The method used is descriptive quantitative. The data collection technique was using a questionnaire and the sampling technique used was random sampling. The sample in this study were customers or buyers of PT. Andalas Citra Elektrindo totaling 100 respondents.